2021
DOI: 10.3390/coatings11030328
|View full text |Cite
|
Sign up to set email alerts
|

High-Temperature Corrosion Behavior of Al-Coated Ni-Base Alloys in Lithium Molten Salt for Electroreduction

Abstract: The electrolytic reduction of a spent oxide fuel involves the liberation of oxygen in a molten salt LiCl–Li2O electrolyte, which creates a corrosive environment for typical structural materials. In this study, the corrosion behaviors of Al–Y-coated specimens in a Li molten salt kept under an oxidizing atmosphere at 650 °C for 72 and 168 h were investigated. The weight loss fraction of the coated specimen to bare specimen was approximately 60% for 3% Li2O and 54% for 8% Li2O at 72 h, and approximately 38% for 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…These reactions are favored by the basic character of the molten salt (high concentration of oxide ion, O 2− ) whose reaction product is soluble in the melt and can precipitate as a porous layer on the surface of the alloy [ 33 ]. The formation of Na 2 CrO 4 and K 2 CrO 4 is favored with increasing temperature; therefore, the corrosion resistance of the alloy could be diminished as its formation depletes the Cr content of the protective layer [ 33 , 34 ]. Recent studies [ 12 ] have shown that Solar Salt dissolves pure Cr by similar reactions.…”
Section: Resultsmentioning
confidence: 99%
“…These reactions are favored by the basic character of the molten salt (high concentration of oxide ion, O 2− ) whose reaction product is soluble in the melt and can precipitate as a porous layer on the surface of the alloy [ 33 ]. The formation of Na 2 CrO 4 and K 2 CrO 4 is favored with increasing temperature; therefore, the corrosion resistance of the alloy could be diminished as its formation depletes the Cr content of the protective layer [ 33 , 34 ]. Recent studies [ 12 ] have shown that Solar Salt dissolves pure Cr by similar reactions.…”
Section: Resultsmentioning
confidence: 99%
“…22 Specifically, during the electrolytic reduction of spent oxide nuclear fuel in a molten lithium salt system containing highly corrosive and strongly basic Li 2 O, the oxygen generated at the anode and resulting high-temperature molten lithium salt can lead to a chemically aggressive environment, which is excessively corrosive for ordinary structural materials. 2,[24][25][26][27][28] Hence, studies on the hot corrosion of Ni-base alloys, which are used to fabricate the equipment related to the handling of high-temperature molten salts owing to their excellent resistance to corrosion at elevated temperatures, [29][30][31][32][33][34][35] have been conducted. In addition, long-term corrosion resistance is an important parameter, which is used to determine the suitability of structural materials requiring continuous exposure to high-temperature molten salts.…”
Section: Introductionmentioning
confidence: 99%
“…Few reports on the high-temperature corrosion behaviours of Ni-base alloys in a LiCl-Li 2 O molten salt are available. [24][25][26][27][28] According to these reports, in addition to the formation, maintenance and spalling of the external corrosion layer and the shape and growth of the internal corrosion layer, the depletion region of major alloying elements formed beneath the corrosion layer has a significant effect on the weight loss of the alloy. Many alloys for hightemperature applications are based on Ni and/or Co due to their better corrosion resistance and rely on the formation of Cr 2 O 3 layers for protection against corrosion.…”
Section: Introductionmentioning
confidence: 99%
“…During the electrolytic reduction of spent oxide nuclear fuel in molten lithium salts, the oxygen generated at the anode and the hot strongly basic lithium oxide make ordinary structural materials highly susceptible to corrosion [6, [31][32][33][34][35]. Therefore, a suitable structural material is required to handle the molten salts during the electrolytic reduction of the spent oxide nuclear fuel.…”
Section: Introductionmentioning
confidence: 99%
“…However, there have been only a few studies on the hot corrosion behavior of Ni-base alloys in molten LiCl-Li 2 O salts [31][32][33][34][35]. According to these studies, the formation, maintenance, and spalling of the external corrosion layer and the shape and growth of the internal corrosion layer as well as the depletion of the major alloying elements beneath the corrosion layer signi cantly affect the weight loss of the alloy.…”
Section: Introductionmentioning
confidence: 99%